Unconventional Monetary Policies and their Impacts on Liquidity of Czech Banking System - Panýr, Tomáš; Brůna, Karel, 1973-; Obešlo, František; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2018)
The master's thesis analyzes the current development of the monetary policy and the implementation of the unconventional monetary instruments by the central banks in response to the financial crisis and a subsequent liquidity trap. Attention is primarily focused on quantitative easing and foreign exchange interventions and their transmission mechanisms by which the monetary authorities seek to fulfill their primary objective in terms of price stability in a zero interest rate environment and a non-functioning standard interest rate transmission. The main objective of the thesis is to link the unconventional monetary policy and the liquidity of the banking system and to explain their close interaction. The analytical part focuses on a specific example of the Czech economy and the implementation of foreign exchange interventions by the Czech National Bank and their influence on the easing of monetary conditions and a further increase in the liquidity of the banking sector.
Vedoucí práce: Karel Brůna
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2018
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2018
Způsob přístupu: Internet
Keywords: finance [obor dipl. práce]; diplomové práce; master's theses